The TRPM4 channel inhibitor 9-phenanthrol alleviates cerebral edema after traumatic brain injury in rats - Ma, Ping; Huang, Ning; Tang, Jun; Zhou, Zunjie; Xu, Jing; Chen, Yi; Zhang, Maoxin; Huang, Qin; Cheng, Yuan (Frontiers in Pharmacology, 2023)
Cerebral edema (CE) exerts an important effect on brain injury after traumatic brain injury (TBI). Up-regulation of transient receptor potential melastatin 4 (TRPM4) in vascular endothelial cells (ECs) results in damage to capillaries and blood-brain barrier (BBB), which is critical for CE formation. 9-phenanthrol (9-PH) has shown an effective inhibition to TRPM4 in many studies. The current study aimed to investigate the effect of 9-PH on reducing CE after TBI. In this experiment, we observed 9-PH markedly reduced brain water content, BBB disruption, proliferation of microglial and astrocytes, neutrophils infiltration, neurons apoptosis and neurobehavioral deficits. At the molecular level, 9-PH significantly inhibited protein expression of TRPM4 and MMP-9, alleviated the expression of apoptosis molecules and inflammatory cytokines such as Bax, TNF-α and IL-6 around injured tissue, and diminished serum SUR1 and TRPM4 levels. Mechanistically, treatment of 9-PH inhibited activation of PI3K/AKT/NF-kb signal pathway, which was reported involving in the expression of MMP-9. Taking together, this study indicates 9-PH effectively reduces CE and alleviate the secondary brain injury partly through the following possible mechanisms: ①9-PH inhibits TRPM4 mediated Na+ influx and reduces cytotoxic brain edema; ②9-PH hinders the expression and activity of MMP-9 by impeding TRPM4 channel and represses the destruction of BBB, thereby preventing vasogenic brain edema. ③9-PH reduces the further damage of inflammation to tissues.